From deep roots to new blooms: The ever‐growing field of evo–devo across land plants. Issue 3 (11th May 2021) - Smith, Stacey D.; Blackman, Benjamin K.
Highlights: This editorial synthesizes the contribution of the articles in the special issue on plant evo‐devo to our understanding of major themes, such as the evolution of developmental signaling, the co‐option and modification of shared genetic toolkits, and the link between microevolution and macroevolution.